Funding liquidity risk of funds of hedge funds: Evidence from their holdings - Vikas Agarwal; George O. Aragon; Zhen Shi (University of Cologne, Centre for Financial Research (CFR), 2015)
We examine the funding liquidity risk of funds of hedge funds (FoFs) by proposing a new measure, illiquidity gap, which captures the mismatch between the liquidity of a FoF's portfolio and the liquidity offered to its own investors. We find that hedge funds that are exposed to the flow-driven sales of FoFs, especially those with higher illiquidity gaps, subsequently exhibit lower abnormal returns. We show that FoFs with greater illiquidity gaps are less likely to be able to access star hedge funds, perform worse during market crises, and have a greater exposure to runs as evident from a higher sensitivity of investor flows to poor performance.
Keywords: 330